2016
DOI: 10.1090/mcom/3085
|View full text |Cite
|
Sign up to set email alerts
|

Avoidability of long 𝑘-abelian repetitions

Abstract: We study the avoidability of long k-abelian-squares and k-abeliancubes on binary and ternary alphabets. For k = 1, these are MĂ€kelĂ€'s questions. We show that one cannot avoid abelian-cubes of abelian period at least 2 in infinite binary words, and therefore answering negatively one question from MĂ€kelĂ€. Then we show that one can avoid 3-abelian-squares of period at least 3 in infinite binary words and 2-abelian-squares of period at least 2 in infinite ternary words. Finally we study the minimum number of disti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…In [24], we answer negatively to (1). Then we modify this question to the following one: Question 4.…”
Section: Final Remarks and Questionsmentioning
confidence: 95%
See 1 more Smart Citation
“…In [24], we answer negatively to (1). Then we modify this question to the following one: Question 4.…”
Section: Final Remarks and Questionsmentioning
confidence: 95%
“…Every infinite binary word contains arbitrarily long abelian squares, while ones exist which avoid squares of period at least 3 [8,25]. We recently showed that one can avoid 3-abelian-squares of period at least 3 over a binary alphabet [24]. It seems natural to ask the following: Question 2.…”
Section: Final Remarks and Questionsmentioning
confidence: 99%
“…Problem 4 ( [14,15]). Can we avoid 2-abelian squares of period at least p on the binary alphabet, for some p ∈ N ?…”
Section: Avoidability Of Long 2-abelian Squaresmentioning
confidence: 99%
“…Thus the largest 2-abelian squares of h 2 (g 3 (h ω 6 (a))) have a period of at most 11 × 5 + 10 = 65. The value 60 is then obtained by checking all the factors of h 2 (g 3 (h ω 6 (a))) of size at most 65. z The value 60 is probably not optimal (the lower bound from [15] is 2). The easiest way to improve this result would be to improve the upper bound on the period for MĂ€kelĂ€'s question.…”
Section: Avoidability Of Long 2-abelian Squaresmentioning
confidence: 99%
“…Such a research was initiated in [12], and later continued, e.g., in [4]. Other topics of the k-Abelian equivalence such as k-Abelian repetitions, k-Abelian palindromicity and k-Abelian singletons were studied in [8,10,11,14], respectively.…”
Section: Introductionmentioning
confidence: 99%